Projovem urbano como política pública de educação: escolarização e inserção profissional dos egressos no município de Imperatriz - MA - RAMOS, Antonia Marcia Meireles (Universidade Federal do Pará, 2014)
This dissertation entitled "Urban Projovem (Programa Nacional de Inclusão de Jovens - National Youth Inclusion Program) as public policy for education: education and employability of graduates in the municipality of the Imperatriz/Maranhão State-MA”, Brazil. It aimed to analyze the impact of Urban Projovem on schooling and on the professionalization of youth; and also it aimed to analyze how the program enabled the students to pursue studies as well as entering the labor market, converging to improve their material, social, spiritual, and cultural conditions. This research was based on the methodological approach of qualitative research and references that take the historical-dialectical materialism as method of data analysis. Data collection was preceded by a literature review followed by field research carrying out semi-structured interviews with seventeen young people coming from the Urban Projovem. It was noted initially that the level of dropout and repetition in Urban Projovem in Imperatriz reaches levels above 50%, similarly to other cities and states of Brazil. With regard to the studies' continuity, most did not continue and the number of young people who could work in the field for which they were qualified represented less than one third of interviewees. Results show that the goals of pursuing studies and inclusion of young people in the labor market have not been achieved. The short time for a more solid formation, the nuclei‟s disintegration with the turnover of teachers, lack of practical lessons regarding the professional qualifications, and the unpreparedness of qualifiers are among the identified problems. However, despite these problems, young people emphasized the program importance for their lives towards personal enhancement with respect to the inclusion sense and belongingness to society, overcoming shyness, sociability, increased self-esteem, relationships with family, independence, and changing in overview about reality and the world. Based on the program dimension, it is concluded that its effects are very small and its emergency nature ensures more a certification than training and social skills of millions of youth and adults.